Penerapan Metode Metode Weighted Aggregated Sum Product Assesment (WASPAS) dalam Pemilihan Supplier - Faisal Amir; Pressa Persana Surya Saputra; Jasmir; Samsul Lutfi; Ni Luh Wiwik Sri Rahayu Ginantra; Ilham Tri Maulana (Journal of Informatics Management and Information Technology, 2023)
The most important activity carried out by companies is to make a profit. Very subjective decision making can lead to errors in supplier selection. In supplier selection, the purchasing department often experiences difficulties in determining the selection of suppliers to be given orders because of the large number of suppliers and the criteria used in the assessment. Therefore, a supplier selection decision support system is needed so that the purchasing department can determine the best supplier. This decision support system uses the Weighted Aggregated Sum Product Assessment (WASPAS) method where this method can be used to overcome existing problems, because there are many alternatives and criteria that must be considered in selecting suppliers such as: price, quality, availability of goods and others. This research will raise a case that is looking for the best alternative based on predetermined criteria. In order to find the weight of each attribute, then a ranking process is carried out which will determine the optimal alternative, namely the best supplier.